Cytotaxonomic studies on some Vicia L. species growing in the eastern Mediterranean and southern Aegean Regions II. - Tabur, S.; Civelek, Ş.; Ba?ci, E. (Akademiai Kiado Rt., 2002)
In this study, some natural Vicia L. species growing naturally in eastern Mediterranean and southern Aegean Regions have been investigated morphological and cytotaxonomic point of view. Morphology, chromosome number and morphometries of the 9 taxa belonging to the Vicia L. genus including Vicia peregrina, V. lutea var. hirta, V. anatolica, V. hybrida, V. grandiflora var. grandiflora, V. grandiflora var. dissecta, V. cuspidata, V. sativa subsp. saliva, V. saliva subsp. nigra var. scgatalis have been studied by using karyological and numerical taxonomic techniques. Data obtained chromosome measurements were analysed by using cluster analysis. The chromosome number of studied Vicia species have been found as 2n = 10, 12 and 14. The member of Vicia section, related taxa were compared with respect to their chromosomal and morphological characteristics. Some karyological relationships among the studied Vicia taxa were discussed with help of taxonomic history and evolutionary data. © 2002 Akadémiai Kiadó, Budapest.
Keywords: Chromosome; Cytotaxonomy; Karyotype; Numerical taxonomy; Vicia